2016
DOI: 10.1021/acsomega.6b00170
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of Promising Molecules for Obtaining Complexes with Planar Tetracoordinate Carbon

Abstract: We have theoretically investigated the stability, chemical bonding, and coordination ability of the 2-Me-2-borabicyclo[1.1.0]but-1(3)-ene (2-Me-2BB) molecule using density functional theory and ab initio molecular dynamics (AIMD) simulations. Calculated results indicated that 2-Me-2BB is both thermodynamically and kinetically stable. The C=C bonds in 2-Me-2BB contain a π bond and a charge shift (CS) bond, different from those in 1-Me-borirene and cyclopropylene. Moreover, 2-Me-2BB can be a σ donor, leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…For example, the energies of A1 and A5 are lower than those of A1 – 1 and A5 – 1 by 30.2 and 49.0 kcal mol −1 , respectively. Thus, in contrast to BHCs, 35 SiBHCs are more stable compared with their linear isomers. In other words, the substitution of SiX 2 for the CX 2 unit in BHCs prefers to form SiBHCs.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…For example, the energies of A1 and A5 are lower than those of A1 – 1 and A5 – 1 by 30.2 and 49.0 kcal mol −1 , respectively. Thus, in contrast to BHCs, 35 SiBHCs are more stable compared with their linear isomers. In other words, the substitution of SiX 2 for the CX 2 unit in BHCs prefers to form SiBHCs.…”
Section: Resultsmentioning
confidence: 95%
“…2, the HOMOs of Ai are mainly the linear combination of the AOs of the two carbon atoms in the C–C bond, which is consistent with those of BHCs. 35,37 According to the π orbital and HOMO, it can be concluded that the C–C bond contains both π and CS bonds analogous to the inverted C–C bond in BHCs. 35 Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Planar tetracoordinate carbon (ptC) has been attracting considerable interest since the ptC concept was first proposed by Hoffman in 1970 . Plenty of compounds with ptC were obtained both experimentally and theoretically, indicating that such compounds with ptC were the new number of the family of carbon. Because silicon and carbon are situated in the same group in the periodic table, planar tetracoordinate silicon (ptSi) was also paid attention by experimental and theoretical researchers.…”
Section: Introductionmentioning
confidence: 99%